2022
DOI: 10.1039/d2tc00836j
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the triplet chromophore environment to prolong the emission lifetime of ultralong organic phosphorescence

Abstract: Molecular environment plays a vital role in regulating the photophysical properties of the optoelectronic functional materials. Here, in a series of phenoxazine derivatives with a triazine core and double-branched structures,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…There is a rise in the C 2 C 6 triplet from 1 to 10 μs, reaching a plateau at ∼20 μs, then finally decaying monoexponentially with a notably long lifetime of 450 μs. This is 2 orders of magnitude longer than the triplet lifetime of C 16 and 2–3 orders of magnitude longer than the triplets of well-known polymers with a similar bandgap such as PCDTBT, APFO3, and IF8TBTT, and over 4 times longer than the low-triplet-energy small-molecule rubrene. , Table S1 compares the triplet lifetime obtained in this work with small molecules and polymers with different bandgaps seen in the literature. ,,, The rise in triplet population on the μs timescale for C 2 C 6 indicates that these triplets are not formed from standard intersystem crossing. Instead, they are formed upon a bimolecular charge recombination process, as can be observed by the C 2 C 6 bimolecular polaron decay kinetics matching the rise of the triplets (Figure S4).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…There is a rise in the C 2 C 6 triplet from 1 to 10 μs, reaching a plateau at ∼20 μs, then finally decaying monoexponentially with a notably long lifetime of 450 μs. This is 2 orders of magnitude longer than the triplet lifetime of C 16 and 2–3 orders of magnitude longer than the triplets of well-known polymers with a similar bandgap such as PCDTBT, APFO3, and IF8TBTT, and over 4 times longer than the low-triplet-energy small-molecule rubrene. , Table S1 compares the triplet lifetime obtained in this work with small molecules and polymers with different bandgaps seen in the literature. ,,, The rise in triplet population on the μs timescale for C 2 C 6 indicates that these triplets are not formed from standard intersystem crossing. Instead, they are formed upon a bimolecular charge recombination process, as can be observed by the C 2 C 6 bimolecular polaron decay kinetics matching the rise of the triplets (Figure S4).…”
Section: Resultsmentioning
confidence: 60%
“…In this study, we report two polymers based on the BDT-T monomer with triplet states with a nearly millisecond lifetime, which are some of the longest triplet lifetimes reported to date for red-emitting conjugated polymer films, closing the gap with blue absorbing molecular crystals. [32][33][34]38,43 This is achieved using two different triplet generation mechanisms. The first is by generating triplets via slow bimolecular electron−hole recombination, and the second by incorporating a Pd porphyrin into the polymer backbone to act as a triplet sensitizer, whereby polymer triplets are formed by back energy transfer from the porphyrin.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…40 We found that the surrounding of the triplet chromophore is critical to regulating the organic phosphorescence lifetime. For example, from a series of phenoxazine-substituted triazine derivatives (29−32) 41 and Cl-substituted carbazole-based isomers (33−35), 42 the intermolecular interactions between chromophores of phenoxazines or carbazoles are gradually weakened by adjusting the manipulation of alky chains and positions of the phenyl ring, resulting in the increase of UOP lifetimes (Figure 3a). Impressively, there is no UOP observed when the electronic coupling between triplet chromophores is weak.…”
Section: Tuning the Emission Lifetimesmentioning
confidence: 99%
“…(a) Manipulation of chromophore environment. Reprinted with permission from ref . Copyright 2022 Royal Society of Chemistry.…”
Section: Property Manipulation Of Uop Materialsmentioning
confidence: 99%
“…Several strategies have been explored to induce efficient phosphorescence from purely organic molecules, such as leveraging n → π* transitions and the heavy-atom effect, which can promote a strong spin–orbit coupling (SOC) process. 4 For instance, Jin et al reported the use of 1,3,5-trifluoro-2,4,6-triiodobenzene (TITFB) as a simple RTP material, demonstrating its potential in promoting n → π* transitions. 5 However, TITFB exhibited weak phosphorescence, limiting its applicability in OLED devices.…”
Section: Introductionmentioning
confidence: 99%